2021
DOI: 10.3390/ijerph18147480
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Fitness Testing to Predict Occupational Performance in Tactical Personnel: A Critical Review

Abstract: Tactical personnel work in an occupation that involves tasks requiring a high level of cardiovascular fitness as well as muscular strength and endurance. The aim of this literature review was to identify and critique studies investigating the relationship between physical fitness, quantified by fitness assessment measures, and occupational task performance. Databases were searched for relevant articles which assessed a fitness measure and a measure of occupational performance. A total of 15 articles were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Prior to establishing occupational standards for both mitigating health-related issues and meeting the demands of essential job tasks, it is necessary to profile the physiological demands of essential job tasks while on duty. Determining these physiological demands may provide additional benefits to law enforcement agencies as many fitness assessments within the law enforcement community have come under scrutiny for failing to be representative of the demands required of qualified police officers ( Orr et al , 2021b , 2021a ). Likewise, determining minimal fitness test scores for hiring and retention is also predicated on determining fitness levels required for the job ( Orr et al , 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to establishing occupational standards for both mitigating health-related issues and meeting the demands of essential job tasks, it is necessary to profile the physiological demands of essential job tasks while on duty. Determining these physiological demands may provide additional benefits to law enforcement agencies as many fitness assessments within the law enforcement community have come under scrutiny for failing to be representative of the demands required of qualified police officers ( Orr et al , 2021b , 2021a ). Likewise, determining minimal fitness test scores for hiring and retention is also predicated on determining fitness levels required for the job ( Orr et al , 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…The extra fitness tests used in this study have been found in the literature to measure one (isolated) aspect of fitness and are therefore good reference tests that can be interpreted unambiguously. Moreover, the procedures adopted during testing are reflective of research incorporating law enforcement populations in the published scientific literature (Cocke et al, 2016;Crawley et al, 2016;Dawes et al, 2016Dawes et al, , 2017Orr et al, 2021).…”
Section: Extra Fitness Testsmentioning
confidence: 99%
“…This test includes components such as push-ups and sit-ups, which are utilized globally in test practices of police organizations. For more practical examples of international fitness tests, we refer to Marins et al (2018), Orr et al (2021) and Zulfiqar et al (2021), among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also have social and psychological obligations (e.g., the daily pace of work, job responsibilities, and stress/risk situations). It appears that the physically demanding jobs require high levels of cardiovascular fitness as well as muscular strength and endurance [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%